IMPLEMENTASI KURIKULUM NASIONAL, INTERNASIONAL, DAN PEMINATAN (OLIMPIADE, PENELITIAN, DAN PROFESIONAL) DI SMA WARDAYA - Luthfia Ulva Irmita; Mia Hilda Amanda; Badrus Syamsi; Anton Wardaya (Universitas Labuhanbatu, 2022)
This study aims to describe and analyze the implementation of the national, international (cambridge) curriculum and specializations (olympics, research, and professionals) at SMA Wardaya. This study uses a qualitative descriptive analysis method. Data collection techniques using triangulation techniques, namely through document studies, interviews, and observations. The research instrument used was a list of interview questions, observation sheets, and student response. The data obtained were then analyzed using an interactive data pattern, including data reduction, data presentation, and drawing conclusions.The results showed that the implementation of national, international and specialization curricula (olympics, research and professionals) at SMA Wardaya could improve the quality of education at SMA Wardaya. This can be seen from the planning, implementation and evaluation of curriculum programs carried out by school principals, representatives of the curriculum, teachers and students are classified as good. In addition, based on questionnaires and observations on the implementation of learning, it also shows that 100% of teachers implement the learning process in accordance with the national, international and specialization curricula (Olympic, research and professional) curricula. The results of the questionnaire on student responses to the implementation of an integrated curriculum of national, international, and specialization (olympic, research, and professional) curriculum at SMA Wardaya showed 75, 60 % of students responded well. Students become more motivated in learning and can develop their skills.